Pirate's price - Anders, Lou (Flight of the Falcon., 2019)
Honda Ohnaka, a space pirate, hero of the Rebellion, and a villain according to Obi-Wan Kenobi. He tells stories of the most amazing ship, the Millennium Falcon, including his very first time onboard and a few occasions where he actually flew the Falcon. It includes some familiar character such as Han Solo and the Wookiee Chewbacca, plus some new characters on these wild rides that's traveling at lightspeed.